2022
DOI: 10.3390/ijerph19020797
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Prevalence and Risk Factors in Three Rural Indigenous Communities of Northern Arizona

Abstract: Helicobacter pylori (H. pylori) is one of the most common bacterial stomach infections and is implicated in a majority of non-cardia gastric cancer. While gastric cancer has decreased in the United States (US), the incidence in the Navajo Nation is nearly four times higher than surrounding Non-Hispanic White populations. Little is known about H. pylori prevalence in this population or other Indigenous communities in the lower 48 states. In this cross-sectional study, 101 adults representing 73 households from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 38 publications
0
18
0
2
Order By: Relevance
“…pylori infection in Native American and Indigenous communities in Alaska is usually higher than their non-native counterparts and is comparable to that of developing countries, which may help explain the high rate of gastric cancer [40][41][42][43][44]. In a random sample of households of three communities on the Navajo Nation, we reported 56.4% prevalence and 72% of households had at least one person with a positive Urea Breath Test [5]. A retrospective study among Navajos living in New Mexico, reported seroprevalence for H. pylori of 74.4%; furthermore, 69.23% of patients with intestinal metaplasia were also positive for H. pylori [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pylori infection in Native American and Indigenous communities in Alaska is usually higher than their non-native counterparts and is comparable to that of developing countries, which may help explain the high rate of gastric cancer [40][41][42][43][44]. In a random sample of households of three communities on the Navajo Nation, we reported 56.4% prevalence and 72% of households had at least one person with a positive Urea Breath Test [5]. A retrospective study among Navajos living in New Mexico, reported seroprevalence for H. pylori of 74.4%; furthermore, 69.23% of patients with intestinal metaplasia were also positive for H. pylori [40].…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer is a complex disease with multiple etiologies each with a differing suite of risk factors [55]. Environmental factors have been shown to play an important role and will need to be considered [5,56]. While it is decreasing in most of the United States, a recent study showed that rates are almost universally higher among American Indians/Alaska Natives compared with geographically proximal White populations [53].…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori infection in Native American and Indigenous communities in Alaska is usually higher than their non-native counterparts and is comparable to that of developing countries, which may help explain the high rate of gastric cancer [ 40 , 41 , 42 , 43 , 44 ]. In a random sample of households of three communities on the Navajo Nation, we reported 56.4% prevalence and 72% of households had at least one person with a positive Urea Breath Test [ 5 ]. A retrospective study among Navajos living in New Mexico, reported seroprevalence for H. pylori of 74.4%; furthermore, 69.23% of patients with intestinal metaplasia were also positive for H. pylori [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer is a complex disease with multiple etiologies each with a differing suite of risk factors [ 60 ]. Environmental factors have been shown to play an important role and will need to be considered [ 5 , 61 ]. While it is decreasing in most of the United States, a recent study showed that rates are almost universally higher among American Indians/Alaska Natives compared with geographically proximal White populations [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation